The Role of Physical Education Teachers in Building Character in Primary School Pupils - Harahap, Indah Aulia Putri (Jurnal Pendidikan, Kesehatan dan Olahraga, 2023)
The purpose of this study is to describe the role of physical education in the character development of students. The task of character based education that combines character development with physical education that can maximise all aspects of the child's development (cognitive, physical, social-emotional, creative and spiritual) is currently needed.This educational paradigm focuses on the development of children as human beings.The method used in this research is a literature review, research sources can be obtained from various sources such as journals, books, documentation, internet, literature and other sources relevant to the research. The data collection technique used in the literature review is by collecting various references and references that are relevant to the topic of the problem under study, using the Google Scholar database by entering the keywords "the role of physical education teachers in building student character". This study found that physical education plays an important role in the formation and cultivation of character in students. The conclusion of this study is that physical education approaches can promote psychological and character development in students.